Effect of different fertilization practices on the growth and yield of cabbage - Hossain, Mohammad Forhad; Farhana, Taneya; Raihan, Md Zahir; Hasan, Md Saeed; Mia, Md Mukul; Rahman, M Mazibur (Asian Journal of Medical and Biological Research, 2015)
The field experiment was conducted at the farmers field of Sutiakhali, a village near the BAU, Mymensingh to investigate effect of integrated nutrient management on yield of cabbage and soil fertility during the period from 5th November 2013 to February2014. The experiment was laid out in Randomized Complete Block Design (RCBD) with three replications and five treatments levels viz. T1: Recommended Dose (RD, N150P53K50S30Zn1.5Bo.7Mo0.5) T2: Soil Test Base (STB, N178P65K51S27Zn1.5B0.7Mo0.5) T3: Integrated Plant Nutrition System (IPNS, N158P59K42S24Zn1.5B0.7Mo0.5) + Cow dung (CD) @ 5.0 tha-1, T4: Farmers Practice (FP, N65P42K71S6) T5: Control (no fertilizer). The Integrated Plant Nutrition System showed significant positive effect on the yield and yield components of cabbage cv. Atlas-70. The results of the present study showed that cow-dung with inorganic fertilizers have significant variation on all the parameters except number of loose leaves. The highest values for plant height (25.88cm), number of folded leaves per head (42.50), length of the biggest leaf (34.77cm), length of the lateral root (31.92 cm), length of stem (6.83cm) were recorded in T3 treatments, on the other hand the highest values in case of number of loose leaves at the treatment of T5 (control). The yield of cabbage crop has increased significantly with application of inorganic fertilizer in combination of cow dung over the control. The highest values for fresh weight of cabbage was 89.16 t ha-1, dry matter content of head (5.93%), dry matter content of loose leaves (9.72%), were recorded at T3 treatments by the application of inorganic fertilizer (N158P59K42S24Zn1.5B0.7Mo0.5) in combination with cow dung @ 5.0 tha-1. The above results indicated that the integrated nutrient management had a remarkable effect in promoting soil fertility and increasing yield and yield components of cabbage. Asian J. Med. Biol. Res. June 2015, 1(2): 182-186